KEY SECURITY INTEGRATION IN THE AES ALGORITHM USING THE LUC ALGORITHM ON IMAGE FILES - Bustami, Harya; Fauzi, Achmad; Khair, Husnul (Yayasan Bina Internusa Mabarindo, 2025)
The rapid growth of information technology requires a reliable data security system, especially for sensitive image files. The Advanced Encryption Standard (AES) is a symmetric algorithm that is fast and efficient; however, its main weakness lies in the vulnerability of key distribution. To address this issue, this research integrates the Lucas (LUC) algorithm to secure AES keys. LUC was chosen as it is an asymmetric algorithm utilizing public and private key pairs, ensuring the confidentiality of AES encryption keys. The purpose of this study is to design and implement an image file security system by integrating AES and LUC using Python programming language with key storage in text format. The encryption process was applied to JPG and PNG files with a maximum size of 3 MB, and the encrypted as well as decrypted results were tested through several experiments. The results indicate that the system successfully encrypted and decrypted image files while maintaining AES key confidentiality through LUC protection. The integration of these two algorithms enhances data security and can serve as a reference for the development of secure digital file systems in the future.